KEWENANGAN UNITED NATIONS COMMITTEE ON THE PEACEFUL USES OF OUTER SPACE (UNCOPUOS) DALAM PEMBENTUKAN HUKUM ANTARIKSA INTERNASIONAL - Diogenes Diogenes (Dialogia Iuridica, 2019)
"The United Nations Committee on the Peaceful Uses of Outer Space" (UNCOPUOS) is a general international organization under the United Nations (UN) system. This committee is the main focal point committee under the United Nations General Assembly (MU) to deal internationally with space issues and issues. UNCOPUOS effectively carried out its duties and mandates in 1961 and has produced several international space law products. The formation of international space law by UNCOPUOS is based on the authority given to it as an international organization. The methodology used in this paper is descriptive juridical-analysis. The type of data used in this study is secondary data (in legal research is called primary legal material), so this study is intended to see the validity of the authority seen from the law of international organizations and the products produced as an international space law. Based on the results of the study, both in terms of the law of international organizations and the content of the results of its legal formation, UNCOPUOS has the authority and the results are legally valid.